Integrative and interactive features of content-based instruction as adopted in the Philippine bilingual context - Otero, Marietta Reyes (The RAP Journal, 2002)
There is greater need to structure the English curriculum to focus directly on the proficiency that the learners need to develop in order to fulfill one of the goals of the Bilingual Education Policy on the use of English. This goal is to meet the needs of the country in the community of nations.